Spatial and Temporal Patterns of Stony Coral Tissue Loss Disease Outbreaks in The Bahamas - Dahlgren, Craig; Pizarro, Valeria; Sherman, Krista; Greene, William; Oliver, Joseph (Frontiers in Marine Science, 2021)
Coral reefs of Grand Bahama and New Providence islands in The Bahamas have been surveyed several times over the past decade and long-term monitoring indicates declines in coral cover associated with hurricanes, bleaching events, and local threats. However, the greatest declines in coral populations in The Bahamas over the past decade may be attributed to the recent introduction of Stony Coral Tissue Loss Disease (SCTLD). In 2019, a comprehensive assessment of both islands was conducted using Atlantic and Gulf Rapid Reef Assessment (AGRRA) methods to characterize reefs before SCTLD was reported in The Bahamas. Following reports of SCTLD in 2020, timed roving diver assessments of corals were conducted for Grand Bahama in and New Providence in 2020 to determine which species were affected and their proportion of colonies that were healthy, infected with SCTLD, and experienced recent mortality. Additional surveys were conducted in January 2021 to further assess the extent of the outbreak, and repeated assessments of several sites for each island were used to determine the impact of the disease on corals over the previous 6 to10 months. Infection rates varied among species following patterns described for Florida and elsewhere, with higher infection rates occurring in vulnerable species for both Grand Bahama and New Providence. Pseudodiploria strigosa was the most affected species with 45.6% of colonies on Grand Bahama infected and 23.1% on New Providence, and recent mortality rates of 31.5% and 42.7% respectively. Mortality and infection rates were greatest close to ports on both islands, and the proportion of healthy colonies increased with distance from the port. Temporal analyses showed an increase in recent mortality and a decrease in active infection for most species on both islands, but little change in the proportion of healthy corals, suggesting some degree of resistance to the disease in the population. Spatial data suggests that SCTLD arrived in The Bahamas via commercial shipping, followed by rapid spread within islands via currents. Results from this study stress the need for early detection and suggest that preventing the spread of the disease between islands via vessel traffic is of utmost importance.